The Ethics by Design Paradigm in Communication Regulation: Countering the Hegemony of Falsehood in Synthetic Media Architecture - Ahmad Sofian; Hasan Sazali; Muhammad Randicha Hamandia; Zhila Jannati (Jurnal Administrasi Pemerintahan Desa, 2026)
This study examines the hegemony of falsehood in synthetic media and the limitations of conventional communication regulation in the age of generative artificial intelligence. Using a critical library-based method, the research synthesizes recent national and international literature, regulatory documents, and platform policy texts to analyze deepfakes, AI-generated disinformation, and post-facto legal responses. The findings show that synthetic media transforms falsehood from a representational distortion into an algorithmically produced reality that is scalable, personalized, and difficult to verify. Indonesia’s current cyber-regulatory framework, including the Electronic Information and Transactions Law, remains largely reactive because it intervenes after harmful content has circulated. This creates epistemological and legal gaps involving velocity, accountability, intent, and platform responsibility. The study proposes Ethics by Design as a future communication policy paradigm that embeds transparency, traceability, algorithmic accountability, privacy protection, and human oversight into system architecture. It concludes that effective synthetic media governance requires shifting from Lex Scripta to Lex Informatica through co-regulation among the state, industry, academics, and civil society.